Augustinian Hermits as the Commissioners and the Audience of Painted Altarpiece in Renaissance Italy - Nazarova, Olga A. (Actual Problems of Theory and History of Art, 2022)
The paper is aimed to outline the specificity of the Italian Augustinian hermits in conceiving and projecting their altarpieces during the Renaissance period. Examination and confrontation of the painted polyptychs, created for the friars’ churches from the earliest known examples of Trecento to those of the 16th century, revealed the recurrence of approaches through the centuries. Like other mendicant congregations, the Austin friars used their altarpiece to represent the key aspects of their order’s identity by visualizing its mission, spiritual practices, and the important representatives of the order or saints chosen as role models. However, the high intellectual culture of the order gave rise to altarpiece programs that stood out for their complex and multilayered meanings. To develop their programs, the friars drew extensively from the theological heritage of their claimed founder and originated unique iconography that finds now parallel in Renaissance art. Their altarpieces, more than any other, required a specific way of perception, the so-called discursive perception, which was based on the viewer’s ability to establish connections between elements, draw parallels, evoke associations and synthesize all into a resulting meaning.The reported study was funded by RFBR according to the research project № 20-012-00524.
Keywords: Augustinian Hermits; Augustinian altarpiece; polyptych; altarpiece iconography; Augustinian iconography; Italian Renaissance painting